Metodologi Periwayatan Hadis - Maulana, Maulana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2002)
The ḥadīth of the Prophet Muhammad (SAW) serves as the second primary source of Islamic teachings after the Qur’an. However, the transmission of ḥadīth differs significantly from that of the Qur’an. While all Qur’anic verses were transmitted through mutawātir (massively transmitted) chains, ḥadīth are classified into mutawātir and āḥād (solitary reports). Consequently, the Qur’an holds the status of qaṭʿī al-wurūd or qaṭʿī al-thubūt, meaning its authenticity is universally accepted. In contrast, ḥadīth, especially those classified as āḥād, require rigorous scrutiny to determine their authenticity. Thus, ḥadīth are generally regarded as ẓannī al-wurūd or ẓannī al-thubūt, indicating their authenticity is probabilistic rather than definitive. While the primary concern in Qur’anic studies is understanding and applying its teachings, the study of ḥadīth encompasses not only comprehension and implementation but also the examination of its transmission. This necessity led to the development of ʿIlm al-Dirāyah, a specialized discipline focused on the methodologies of ḥadīth transmission. This paper explores the methodologies of ḥadīth transmission, including the conditions for acceptance and narration, different methods and forms of transmission, and efforts in ḥadīth dissemination. It begins by defining and comparing al-riwāyah and al-shahādah, followed by a discussion on scholarly differences and the author’s analytical perspective.